2018
DOI: 10.1007/s11845-018-1803-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors associated with acquiring measles in an outbreak among age-appropriately vaccinated school children: a cohort analysis

Abstract: The reason for intense measles activity in one class was not established. Although a concurrent investigation into cold chain and vaccine stock management did not identify a cause for the high relative risk of measles in children vaccinated, recommendations were made for improving cold chain and vaccine stock management in General Practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Also, the risk was significantly higher for those who received the last dose of MMR vaccine 5 or more years ago. This has actualized the issue of the MMR vaccine effectiveness in protecting against mumps and considering changing the vaccine calendar (18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the risk was significantly higher for those who received the last dose of MMR vaccine 5 or more years ago. This has actualized the issue of the MMR vaccine effectiveness in protecting against mumps and considering changing the vaccine calendar (18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested the possibility (and some have proven) that there is a difference between the genotype of the circulating Mumps virus and that in MMR vaccines, and a potential cold chain disruption was previously recognized as a potential cause for the lack of protective effect of the MMR vaccine and which is essential for this vaccine to be maintained (stored at +2 to + 8° C, in a dark place for up to one hour before administration). It should be noted that genotyping of the circulating Mumps virus is not done routinely, and cold chain surveillance is an obligation of the services that are in charge of implementing national immunization programs (18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%